A Cognitive Linguistic Study of Image Schemata in Selected English Proverbs - Abdul-Sada Atia, Alya'a; Muhsin Gharab , Ali (Journal of College of Education, 2020)
This study intends to examine image schemata in English proverbs based on the Johnson’s image schemata types in a cognitive semantic approach. Thus, the present study considers firstly some theories concerning cognitive linguistics, cognitive semantics, image schemata and its types. Then it examines the three categories of the Johnson’s (1987) image schemata, namely, container, force, and path image schemata. The fundamental aim of the study is to answer a set of questions such as (1) what are the main types of Johnson’s image schemata in English proverbs? (2) How do image schemata play a dynamic role in structuring human physical experiences even before learning a language? (3) In which way does the use of certain linguistic items redound on deciding the type of image schemata? However, the consequences of the current study show that (1) Some of English proverbs contain Johnson’s types of image schemata, namely, container, force, and path schemata, (2) image schemata have an experiential basis, and (3) the meaning of most of image schemata in English proverbs is associated with using certain linguistic items.